Early-Stage Supraglottic "In Situ" Squamous Cell Carcinoma of the Larynx Incidentally Detected by 18F-Fluorocholine PET/CT. (July 2019) - Mangili, Stefano Attilio; Rizzardi, Nicola; Illuminati, Sonia; Bnà, Claudio; Savelli, Giordano
Abstract : Abstract: 18 F-fluorocholine ( 18 F-FCH) PET/CT is widely used to study patients affected by prostate cancer. Despite its specificity, however, 18 F-FCH may be taken up by other neoplasms such as multiple myeloma, lymphomas, lung, bladder, and colon cancer; brain tumors; and renal and hepatocellular carcinoma. This is due to its ability to evaluate the cell proliferation, which is typical of neoplastic cells. While this behavior may be an opportunity to image more neoplasms, on the other hand it could represent a source of error in the evaluation of the images. Here we present the case of a laryngeal squamous cell carcinoma detected by 18 F-FCH.